PERAN KULIAH KERJA NYATA (KKN) DALAM MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS (SDGS) DI DESA WANAHERANG - Bahrudin, Canra; Az-Zahra, Mawalida; Ajizah, Hikmah; Izzati, Ilmi; S., Indi Viona; Jaenuddin; Julianti; Husniati, Nia; Aulia, Putri Patwa; Maulida, Zalfa; Muliana (Servirisma, 2024)
Abstrak Real Work Lecture Activities (KKN) are a form of activity that provides students with learning experiences to live in the community outside campus. KKN activites also function as a learning process and service to developing communities and directly identify and handle various development problems being faced by the community. KKN is carried out by universities in an effort to increase the mission and weight of education for students to get greater added value in higher education. The implementation of KKN is a manifestation of the fourth catur dharma of higher education, namely community service. Development and resettlement of disadvantaged areas (Kemenkes PDTT) carries out programs to implement the sustainable development goals. This program, which is also known as sustainable development goals (SDGs), is regulated in Presidential Regulation Number 59 of 2017 concerning village SDGs in Wanaherang Village. Keywords: Real Work Lectures, Sustainable Develompent Goals